Systems kinomics for characterizing host responses to high consequence pathogens at the NIH/NIAID Integrated Research Facility-Frederick. Issue 2 (1st July 2014) - Kindrachuk, Jason; Falcinelli, Shane; Wada, Jiro; Kuhn, Jens H.; Hensley, Lisa E.; Jahrling, Peter B.
Abstract: Currently, there is a paucity of information regarding the molecular pathogenesis for many high consequence pathogens (HCPs) that pose threats to both national and international public health. In spite of this, investigations of the molecular pathogenesis for many HCPs have been limited to gross pathological changes in animal models or global analysis of gene expression. Further, questions remain regarding the ability of animal models of disease to recapitulate human molecular pathogenesis or act as predictors of therapeutic efficacy. Thus, it is likely that medical countermeasure development for HCPs will rely on identifying therapeutic targets that are uniquely modulated during HCP infection. It is also appreciated that many cellular processes can be regulated independently of changes in transcription or translation through phosphorylation events. Cellular kinases, individually or collectively (the kinome), play critical roles in regulating complex biology, underlie various malignancies, and represent high priority drug targets. The growing interest in kinases in both basic and translational research has driven efforts to develop technologies that enable characterization of phosphorylation mediated signal transduction. To this end, enhanced technical capabilities at the IRF Frederick provide the unique capability for characterizing host responses to HCP insult during the course of infection and identify novel targets for therapeutic intervention. Abstract : Kinome analysis at the IRF Frederick to identify novel information regarding the molecular pathogenesis of high consequence pathogens and novel therapeutic targets. Abstract :